Explaining continuance intention to use telemedicine among adult patients in Jakarta, Indonesia: An extended UTAUT2, trust, and satisfaction structural equation modeling - Mochamad Dandi (Privietlab, 2026)
Telemedicine has become a key pillar of Indonesia’s digital health transformation, but its long-term impact depends on whether patients keep using it after the urgency of the pandemic fades. Jakarta offers a strong research setting due to its high healthcare demand, solid digital infrastructure, diverse population, and direct exposure to national telemedicine policies. This study proposes a structural equation modeling approach to analyze continuance intention among adult telemedicine users in Jakarta. It integrates the Unified Theory of Acceptance and Use of Technology 2 with additional factors such as telemedicine service quality, eHealth literacy, trust, satisfaction, privacy concern, and affordability. Data will be collected through a cross-sectional survey targeting Jakarta residents aged 18 and above who have used telemedicine at least once in the past 12 months. The study aims to gather 400–500 valid responses through healthcare facilities, community networks, and online patient groups across Jakarta. All variables will be measured using seven-point Likert scales and analyzed with partial least squares structural equation modeling. The measurement model will assess reliability, composite reliability, average variance extracted, discriminant validity, and common method bias. The structural model will evaluate path coefficients, bootstrapped confidence intervals, explained variance, predictive relevance, and mediation effects. The hypotheses suggest that performance expectancy, effort expectancy, facilitating conditions, eHealth literacy, price value, trust, and satisfaction positively influence continuance intention, while privacy concern negatively affects trust and potentially reduces usage intention. Telemedicine service quality is expected to enhance trust and satisfaction, which then mediate continuance intention. Overall, this study contributes practical insights for improving patient-centered telemedicine services in Indonesia’s post-pandemic context.